The Benefits Of Self-Healed Healing Each Up The Workload Of Officers Towards Reducing The Pain Scale Of Post-Operative Patients - Hanifah, Astin Nur; Ilham, Radiah; Suabey, Suningsih; Tondok, Santalia Banne; Halitopo, Yoel; Rahmat, Rezqiqah Aulia; Idris, Idris (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Self-healing can be done in various ways, one of which is through meditation and therapeutic touch. There is a similar journal about reducing pain using Therapeutic touch. The purpose of this study was to determine the effect of self-healing (healing touch) on reducing pain sensation in post-op patients at the Regional General Hospital. This study uses a quasi-experimental method with a pretest and posttest design. The population in this study were all postoperative patients treated at the Regional General Hospital. The results of the study showed that the difference in the results of the pain scale after receiving self-healing intervention was a decrease in the pain scale in respondents who received self-healing. Based on the results of the study, it can be concluded that the study conducted provides a description of the characteristics of post-op patients at the Regional General Hospital consisting of 39 respondents, most of whom were 36-45 years old with the majority of female gender and dominated by patients who work as housewives. There was a significant difference in the decrease in the level of pain in post-op patients after the influence of self-healing in the intervention group with an average decrease. There is an influence of self-healing on reducing pain levels in post-op patients.